Immunobiology of pulmonary fibrosis - Bindu, Samik; Yasmin, Hadida; Barman, Uttam; Pandit, Subhradip; Masmoudi, Khaled; Kishore, Uday (Frontiers in Immunology, 2025)
Pulmonary fibrosis, an interstitial lung disease, is characterized by progressive thickening and scarring of the lung tissue associated with shortness of breath, decreased vital capacity, and respiratory failure due to the inability to expand and contract the lungs during inspiration with severe morbidity and mortality. The median estimated survival is 2–5 years following diagnosis. Current understanding of how the disease initiates and progresses suggests a set of complex mechanisms involving genetic vulnerability, aging processes, and environmental factors. Mechanistically, the damage of the alveolar epithelial cells (AECs) (type I and type II), followed by recruitment of immune cells and transdifferentiation of fibroblast to myofibroblast play a crucial role in the initiation of a prolonged wound healing response in lungs which eventually leads to fibrosis if healing gets awry. Here, we have systematically reviewed the role of innate and adaptive immunity, as well as interactions of lung parenchyma cells together with the immune cells, cytokines, chemokines and other mediators in the context of pulmonary fibrosis. We have also discussed how the selection of pre-clinical models is important for understanding the disease and successful clinical trial outcome.